Hepatitis C–Some New Treatment Options - Ehsan-ul-Haq, (Journal of University Medical & Dental College, 2020)
Hepatitis C Virus (HCV) infection is a major world health problem It is one of the main causes of cirrhosis and Hepatocellular Carcinoma (HCC). HCV-related end stage liver disease is the leading reason for liver transplantation in the USA. The introduction of routine screening of blood, blood products and organ tissues has reduced transmission in advanced economies. Unfortunately this is not the case in developing economies where poor screening, unreliable blood screening tools, careless attitude of the laboratory personnel and poor economic status of the patient all contribute to the unabated incidence of new cases